Rwanda : Sixth Review Under the Policy Coordination Instrument and Monetary Policy Consultation Clause-Press Release; Staff Report; and Statement by the Executive Director for Rwanda. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2022)
The economy has emerged from the COVID-19 pandemic with scars that would likely take time to reverse. Supported by the authorities' policy support, growth rebounded strongly to 10.9 percent in 2021. Spillovers from the war in Ukraine are compounding pandemic challenges by weighing on growth, increasing inflationary pressures and social needs, and straining fiscal balances amid high uncertainty and rising food insecurity concerns. Lower external demand and higher global commodity prices are projected to lower growth to 6 percent in 2022. Headline inflation is projected to rise from 0.8 percent in 2021 to 9.5 percent in 2022, exceeding the central bank's benchmark level (5 percent). The National Bank of Rwanda (NBR) raised the policy rate by 50 basis points in February 2022. While the near-term outlook is marred by uncertainty from the geopolitical risks that could prolong the spillovers from the war in Ukraine, the medium-term outlook remains favorable, supported by the authorities' commitment to structural reforms. The change in World Bank financing terms under IDA20 will increase the volume of loans, hence the debt-to-GDP ratio for Rwanda, but given the higher concessionality of the loans, the expected impact on the present value of debt path is marginal.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Rwanda